(untitled) (Jurnal Destinasi Pariwisata, 2025)
Tenganan Pegringsingan Tourism Village, as one of the Bali Aga villages, is an example of a tourist village that preserve a rich value of customs and traditions in sacred nuances. In the midst of the rapid development of tourism in Bali, Tenganan Tourism Village faces significant challenges in preserving its cultural authenticity and sacred values without being eroded by commercialization flow. This study aims to identify the challenges and strategies applied by the Tenganan Tourism Village community in maintaining the synergy between sacredness and tourism, so that traditional values can be preserved. The research approach is qualitativedescriptive using interview methods, direct observation, and literature review, including lontar which is the basis of customary law. The results show that the main challenges faced by the village are the pressure of commercialization, tourist’s ignorance of the sacred value, and the influence of external culture to the youth generation. To overcome these challenges, Tenganan Tourism Village implemented a strategy based on awigawig (customary law), limiting the access to sacred areas, developing educational tourism, and implementing community-based tourism. The synergy between sacredness and tourism in Tenganan Pegringsingan Tourism Village highlights that tourism is sustainable with customs and sacred values by managing the approach of respect with the local values. By implementing this strategy, Tenganan Tourism Village has managed to maintain its cultural identity and provide a model of sustainable tourism village without sacrificing traditional values. This research contributes in providing insights to the management of other tourism villages that face similar challenges in preserving traditions and sacred values in the midst of modern tourism.